Age–Sex Class Variation in the Activity Budget and Diet of Rhinopithecus bieti in Association with Monthly Temperature - Jacob B. Kraus; Zhi Pang Huang; Yan Pang Li; Liang Wei Cui; Shuang Jin Wang; Jin Fa Li; Feng Liu; Yun Wang; Karen B. Strier; Wen Xiao (International Journal of Primatology, 2026)
The energy and nutrient costs associated with body mass, age, and sex can influence variation in primate behavior and diet. However, comparatively little is known about how these factors affect the behavioral and dietary flexibility of Asian colobines in response to intra-annual climate shifts. We collected data on an isolated population of black-and-white snub-nosed monkeys ( Rhinopithecus bieti ) at Mt. Lasha in the Yunling Provincial Nature Reserve, Yunnan, China, using instantaneous and scan sampling across 32 months between May 2008 and August 2016 to assess the association of temperature on the activity budgets and diets among and within age-sex classes. Adult females spent more time feeding, juveniles spent more time moving and less time resting, and adult males spent less time moving and more time resting than other age-sex classes. We did not detect any significant variation in diet across age-sex classes. This population spent more time feeding and less time moving and resting in colder months than in warmer months; however, we only detected these temperature-related effects within age-sex classes for moving and resting, not feeding. This population also spent more time feeding on lichen during colder months than during warmer months, a finding that cannot be explained by temperature-related dietary shifts within age-sex classes because their diets remained stable throughout the year. Our results suggest that intra-annual variation in temperature may amplify the distinct physiological demands among different age-sex classes, leading to greater shifts in activity patterns than in diet composition.